Altered thyroid status affects myocardial expression of connexin-43 and susceptibility of rat heart to malignant arrhythmias that can be partially normalized by red palm oil intake - Bačová, Barbara Szeiffová; Vinczenzová, Csilla; Žurmanová, Jitka; Kašparová, Dita; Knezl, Vladimír; Egan Benová, Tamara; Pavelka, Stanislav; Soukup, Tomáš; Tribulová, Narcisa (Histochemistry and cell biology, 2017)
We aimed to study the impact of altered thyroid status on myocardial expression of electrical coupling protein connexin-43 (Cx43), the susceptibility of rats to ventricular fibrillation (VF) and the effects of antioxidant-rich red palm oil (RPO). Adult male and female euthyroid, hyperthyroid (treated with T3/T4), hypothyroid (treated with methimazole) Wistar rats supplemented or not with RPO for 6 weeks were used. Function of isolated perfused heart and VF threshold were determined. Left ventricular tissue was used for assessment of mRNA and protein levels of Cx43, its phosphorylated forms and topology. Protein kinase C signaling (PKC) and gene transcripts of some proteins related to cardiac arrhythmias were assessed. Hyperthyroid state resulted in decrease of total and phosphorylated forms of Cx43 and suppression of PKC-ε expression in males and females, decrease of Cx43 mRNA in females, decrease of VF threshold and increase of functional parameters in male rat hearts. In contrast, hypothyroid status resulted in the increase of total and phosphorylated forms of Cx43, enhancement PKC-ε expression in males and females, increase of Cx43 mRNA in females, increase of VF threshold and decrease of functional parameters in male rat hearts. Function of the heart was partially normalized by RPO intake, which also enhanced myocardial Cx43 and PKC-ε expression as well as increased VF threshold in hyperthyroid male rats. We conclude that there is an inverse relationship between myocardial expression of Cx43, including its functional phosphorylated forms, and susceptibility of male rat hearts to VF in condition of altered thyroid status. RPO intake partly ameliorated adverse changes caused by excess of thyroid hormones.
Keywords: potkani Wistar; Thyroid Gland; srdeční arytmie; RNA, Messenger; aplikace orální; Rats, Wistar; štítná žláza; konexin 43; Administration, Oral; Heart; srdce; Rats; zvířata; Animals; Female; Male; Arrhythmias, Cardiac; mužské pohlaví; Myocardium; Plant Oils; messenger RNA; Connexin 43; ženské pohlaví; krysa rodu Rattus; oleje rostlin; myokard